Rekonstruksi Teologi Relasional Injil Yohanes Sebagai Model Pembinaan Iman Dalam Konteks Pluralisme Indonesia - Anthony Kurniawan Wyatno; Laurentius Prasetyo (Institut Agama Kristen Negeri (IAKN) Ambon, 2026)
Abstract : This study addresses a critical gap in Johannine scholarship, which has long been dominated by Western theological approaches that tend to emphasize metaphysical christological and symbolic dimensions, while providing limited exploration of relational aspects within pluralistic societies. The purpose of this research is to reconstruct the relational theology of the Gospel of John as an applicable model for faith formation in the context of Indonesian pluralism. Employing an integrative qualitative theological approach—combining biblical exegesis, narrative criticism, and contextual hermeneutics on John 1:1–18, John 6, and John 15—this study identifies relational ontology as the core of Johannine theology. The findings reveal that faith, from John’s perspective, is not merely cognitive-doctrinal acceptance, but rather an existential participation (menō) in divine relationship that manifests love as a dialogical bridge across differences. The novelty of this research lies in its systematic synthesis between biblical analysis and contextual praxis, resulting in the paradigm of “Johannine Relational Theology.” This model contributes theoretically to mitigating religious polarization and offers a new direction for dialogical faith formation in pluralistic societies. Keywords: Gospel of John, Relational Theology, Faith Formation, Pluralism, Indonesia